Comparison of simple models for total nitrogen removal from agricultural runoff in FWS wetlands. (1st June 2022) - Canet-Martí, Alba; Grüner, Sabrina; Lavrnić, Stevo; Toscano, Attilio; Streck, Thilo; Langergraber, Guenter
Abstract: Free water surface (FWS) wetlands can be used to treat agricultural runoff, thereby reducing diffuse pollution. However, as these are highly dynamic systems, their design is still challenging. Complex models tend to require detailed information for calibration, which can only be obtained when the wetland is constructed. Hence simplified models are widely used for FWS wetlands design. The limitations of these models in full-scale FWS wetlands is that these systems often cope with stochastic events with different input concentrations. In our study, we compared different simple transport and degradation models for total nitrogen under steady- and unsteady-state conditions using information collected from a tracer experiment and data from two precipitation events from a full-scale FWS wetland. The tanks-in-series model proved to be robust for simulating solute transport, and the first-order degradation model with non-zero background concentration performed best for total nitrogen concentrations. However, the optimal background concentration changed from event to event. Thus, to use the model as a design tool, it is advisable to include an upper and lower background concentration to determine a range of wetland performance under different events. Models under steady- and unsteady-state conditions with simulated data showed good performance, demonstrating their potential for wetland design. HIGHLIGHTS: The most robust model combination: the tanks-in-series model under steady conditions. First-order kinetics with non-zero background concentration was the best for degradation. The optimal background concentration changed from event to event. Potential use of TIS model in unsteady conditions when infiltration and evapotranspiration occur. Graphical Abstract